2022
DOI: 10.3390/ijms23105851
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Disorders, Renal Impairment and Growth in Mucopolysaccharidosis-Plus Syndrome

Abstract: Mucopolysaccharidoses (MPS) are rare lysosomal storage disorders (LSD) characterized by the excessive accumulation of glycosaminoglycans (GAG). Conventional MPS, caused by inborn deficiencies of lysosomal enzymes involved in GAG degradation, display various multisystemic symptoms—including progressive neurological complications, ophthalmological disorders, hearing loss, gastrointestinal and hepatobiliary issues, cardiorespiratory problems, bone and joint abnormalities, dwarfism, and coarse facial features. Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Sofronova et al recently reported on progressive hematopoietic abnormalities noted in MPS-PS patients, especially in the red blood cells and platelets; however, we did not observe any of them [ 14 ]. They also observed that most patients experienced elevated levels of uric acid in the blood as a manifestation of kidney failure.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Sofronova et al recently reported on progressive hematopoietic abnormalities noted in MPS-PS patients, especially in the red blood cells and platelets; however, we did not observe any of them [ 14 ]. They also observed that most patients experienced elevated levels of uric acid in the blood as a manifestation of kidney failure.…”
Section: Discussioncontrasting
confidence: 82%
“…Growth retardation, as well as poor weight gain, were also observed in several patients reported by Sofronova et al [ 14 ]. Contrary to that, our patient had normal growth (see Figure 2 ) and was overweight (visceral obesity).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Immune deficiency caused by impaired development of NK cells and cytotoxic T cells has been documented in lysosomal biogenesis defects and abnormal endosomal-lysosomal trafficking (Ham, 2014; Orange, 2008; Ballabio, 2020). Finally, the severe nephritis with glomerular sclerosis and proteinuria is likely to be related to vacuolation and effacement of podocytes in which active endocytosis is impaired (Chen, 2013; Bechtel, 2013; Sofronova, 2022).…”
Section: Discussionmentioning
confidence: 99%